Leaky Genres, Leaky Subjects: Religious Authority and the Presentation of the Self in a Feminizing Muslim Public Sphere. - Kloos, David (Social Analysis, 2025)
In Malaysia, women Islamic preachers use various rhetorical devices and performative styles to (re)shape Islamic gender norms. Focusing on preacher, novelist, and influencer Fatima Syarha, who offers compelling guides for pious life and professional ambition, this article asks how these preachers establish their authority in a public sphere that has become increasingly polarized between secular liberalism and religious conservatism. The answer, it argues, lies in the maximization of the creative possibility of genre to simultaneously extend and subtly subvert religious traditions. Crafting experimental and flexible genres through mixing theology, self-help, and fictionalized accounts of the religious self, some of these women preachers develop new registers of authority. Creatively experimenting with the presentation of the self, they situate women simultaneously at the center and at the receiving end of the Islamic tradition.